3D hierarchical local heterojunction as ultra-highly efficient Fenton-like catalyst: Mechanism of coupling the proton-coupled electron transfer under nanoconfinement effect. Issue 3 (June 2022) - Nie, Fan; Xu, Wenyue; Zhang, Di; Wang, Junwei; Zhang, Ruixue; Fang, Xiaojie; Wang, Yaxin
Abstract: Charge transfer in general type-II heterojunction is hard to realize and the transfer mode weakens the overall redox ability of the heterojunction. Band regulation and surface interface structural modifications assembled a novel visible-light-driven homogeneous catalyst (FeS2 anchored on Mo2 C aerogel), which activated the peroxymonosulfate (PMS) by proton-coupled electron transfer effect under the nanoconfinement effect. The degradation rate constant of the FeS2 @Mo2 C/PMS system is 11.4 times that of the PMS system and 2.6 times that of the Fe(Ⅱ) + Mo2 C + PMS Fenton-like system. The initial pH has almost no effect on the degradation rate of the FeS2 @Mo2 C/PMS system. The EPR results show that the FeS2 @Mo2 C heterostructure can effectively catalyze the production of SO 4 · −, HO · and 1 O 2 by PMS, which is in agreement with the quenching results. DFT calculations demonstrate the existence of stable SMo bonds in FeS2 @Mo2 C Schottky junctions. Thus S vacancies in FeS2 significantly accelerated the transfer of FeS2 photogenerated electrons to Mo2 C, FeS2 photogenerated holes can directly oxidize Azo dyes, extensively promoting the catalytic oxidation reaction rate. The prepared mesoporous catalysts (average pore diameter = 58.13 nm) through nanoconfinement effect can effectively accelerate the transmission speed to achieve the target pollutants > 99.9% removal rate in five min under sufficient catalyst. This paper provides a new perspective on applying Schottky heterojunctions coupled with photocatalytic technology for the effective degradation of Azo dyes. Graphical Abstract: ga1 Highlights: Schottky heterojunction of Mo2 C and FeS2 is formed by chemical deposition and electrostatically driven self-assembly. PMS activated by proton-coupled electron transfer under nanoconfinement effect. The target pollutants > 99.9% removal rate in five min under sufficient catalyst. DFT calculations demonstrate the existence of stable SMo bonds in FeS2 @Mo2 C Schottky junctions. After five cycles of experiments, the catalytic activity is > 95%.